2011
DOI: 10.1007/s11605-011-1716-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Percutaneous Ablation in Very Early-Stage Hepatocellular Carcinoma

Abstract: Treatment of very early-stage HCC using a multimodal strategy tailored to tumor characteristics achieves equivalent initial CR rates and long-term survival rates compared to surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
(40 reference statements)
3
31
1
Order By: Relevance
“…The 10 included studies comprised one RCT, 14 eight retrospective observational studies, 15,16,[29][30][31][32][33][34] and one non-randomized prospective comparison trial. 17 Study characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 10 included studies comprised one RCT, 14 eight retrospective observational studies, 15,16,[29][30][31][32][33][34] and one non-randomized prospective comparison trial. 17 Study characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of satellite nodules and platelet counts <150,000/μl are independently associated with survival, whereas the presence of satellite nodules and cirrhosis and the use of nonanatomic resection are independently associated with tumor recurrence [10]. Percutaneous ablation can achieve an acceptable outcome for very earlystage HCC: a 5-year disease-free survival rate of 62% and a 5-year overall survival rate of 78% [11]. Furthermore, it has been suggested that radiofrequency ablation (RFA) leads to better overall survival in patients with operable HCC than in those with inoperable HCC.…”
Section: Therapeutic Strategies Based On Hcc Stagementioning
confidence: 99%
“…Livraghi and colleagues [19] reported a complete response rate of 97.2% and a 5-year survival rate of 68% in 218 patients with very early-stage HCC treated using RFA. In another recent study [39] of 83 patients with very early HCC who were treated using different modalities of percutaneous ablation (33 PEI, 19 MW, and 31 RFA), the complete response rate was 95%, and the 5-year survival rate was 78%. Therefore, RFA is suggested by some authors as first-line therapy for very early-stage HCC, and surgical resection is reserved for when individual patient variables render RFA unfeasible or unsafe [40].…”
Section: Very Early Stage (0)mentioning
confidence: 98%